CONSTRUCTIVIST PEDAGOGICAL MODELS FOR DEVELOPING SKILLS THROUGH CHROMATOGRAPHIC PROBLEM-SOLVING TASKS. - Abduraximova Shahlo Azim qizi; Kosimova Xurshida Rajabboyovna (Research Focus International Scientific Journal, 2025)
This article explores the application of constructivist pedagogical models in teaching chromatographic analysis, with a focus on skill development through problem-solving tasks. The research emphasizes how learners actively construct knowledge by engaging in hands-on chromatographic exercises that simulate real-world analytical problems. Various teaching strategies rooted in constructivist theory—such as inquiry-based learning, collaborative experiments, and reflective thinking—are examined for their effectiveness in enhancing students’ analytical competencies. The paper also provides a methodological framework for integrating chromatographic problem-solving into the chemistry curriculum, contributing to the development of higher-order thinking skills and scientific literacy. Findings suggest that constructivist approaches significantly improve students’ conceptual understanding, engagement, and practical skills in chromatographic analysis.